Analisis Profitabilitas dan Tingkat Kesejahteraan Petani Bawang Merah di Kecamatan Mijen Kabupaten Demak - inayah rahmawati putri utami; Wiludjeng Roessali; Siwi Gayatri (Fakultas Pertanian, Universitas Timor, 2023)
The shallot commodity has a high economic value and is widely used as the main ingredient for basic cooking ingredients in Indonesia, besides that it is also used as a medicinal ingredient. Demak Regency is one of the shallot production centers in Central Java. The contribution of red onion production in Demak Regency to provincial production is 13%. Shallot farming in Indonesia still faces many obstacles, including in Demak Regency. These farming constraints include the threat of land conversion, the price of high-quality seeds and the not optimal use of production inputs. The purpose of this study was to analyze the income and profitability of shallot farming, household expenses of shallot farmers in Mijen District, Demak Regency and the level of welfare of shallot farming households in Mijen District, Demak Regency. The samples taken in this study were shallot farmers as many as 96 respondents who were determined using the slovin formula with an error rate of 10%. Based on the results of the analysis, the income of shallot farmers in Mijen District, Demak Regency was Rp. 119,188,411.00 with an average farmer's land area of 7600 m2. The profitability value is 169.67% where the BRI Bank deposit interest rate at the time of this study was 3.75%, meaning that the shallot farming in Mijen District is feasible to run. The total household expenditure of shallot farmers in the District is IDR 88,039,262/MT. This expenditure consisted of farming expenses of IDR 70,117,256 and non-farming expenses of IDR 17,922,006. The exchange rate for the household income of shallot farmers is 1.48, which is greater than 1, meaning that the welfare level of the farmers has entered the prosperous group.